Profil penalaran matematis dalam menyelesaikan pertanyaan pola bilangan didasarkan pada peminatan tahfidz dan non-tahfidz di Pondok Pesantren Putri Al-Hikmah Al-Fathimiyah - Afidatuzzaro, Nurul (Maliki Interdisciplinary Journal, 2024)
This research is a qualitative research type to describe the subject’s mathematical reasoning ability in solving number pattern questions in terms of the subject’s specialization at the Al-hikmah Al-fathimiyah girls’ boarding school in Malang. The subjects in this research were female students from PPP. Al-hikmah Al-Fathimiyah with a total of 4 subjects grouped based on specialization taken at the Islamic boarding school. The division of subjects is based on 1) tahfidz with high skills 2) tahfidz with medium skills 3) non-tahfidz with high skills, and 4) non-tahfidz with a moderate skill. The data collection technique used was giving tests and interviews. The instruments used were test sheets and interview guides. Data analysis was carried out by data reduction and inference. Meanwhile, to test the validity of the data, the triangulation method was used. Based on this research, it is known that tahfidz subjects tend to use certainty and remember the concepts taught before working on and completing questions. Meanwhile, non-tahfidz subjects tend to use feeling and reason about whether the answer matches the question.